Genetically driven CD39 expression shapes human tumor‐infiltrating CD8+ T‐cell functions. Issue 9 (8th July 2020) - Gallerano, Daniela; Ciminati, Selina; Grimaldi, Alessio; Piconese, Silvia; Cammarata, Ilenia; Focaccetti, Chiara; Pacella, Ilenia; Accapezzato, Daniele; Lancellotti, Francesco; Sacco, Luca; Caronna, Roberto; Melaiu, Ombretta; et al.
Abstract: In our study, we investigated the role of CD39 on tumor‐infiltrating CD8 + T lymphocytes (CD8 + TILs) in colorectal, head and neck and pancreatic cancers. Partially confirming recent observations correlating the CD39 expression with T‐cell exhaustion, we demonstrated a divergent functional activity in CD39 + CD8 + TILs. On the one hand, CD39 + CD8 + TILs (as compared to their CD39 − counterparts) produced significantly lower IFN‐γ and IL‐2 amounts, expressed higher PD‐1, and inversely correlated with perforin and granzyme B expression. On the other, they displayed a significantly higher proliferative capacity ex vivo that was inversely correlated with the PD‐1 expression. Therefore, CD39 + CD8 + TILs, including those co‐expressing the CD103 (a marker of T resident memory [TRM] cells), were defined as partially dysfunctional T cells that correlate with tumor patients with initial progression stages. Interestingly, our results identified for the first time a single nucleotide polymorphism (SNP rs10748643 A>G), as a genetic factor associated with CD39 expression in CD8 + TILs. Finally, we demonstrated that compounds inhibiting CD39‐related ATPases improved CD39 + CD8 + T‐cell effector function ex vivo, and that CD39 + CD8 + TILs displayed effective suppression function in vitro. Overall these data suggest that the SNP analysis may represent a suitable predictor of CD39 + CD8 + T‐cell expression in cancer patients, and propose the modulation of CD39 as a new strategy to restore partially exhausted CD8 + TILs. Abstract : What's new? CD39 is an enzyme expressed by regulatory T cells (Treg), which can suppress anti‐tumor immune responses. Recent studies have found that CD39 is also expressed by subsets of CD8+ tumor‐infiltrating lymphocytes (TILs). In the current study, the authors found that inhibiting CD39 can restore CD8+ TIL function. They also identified a SNP that may help predict dysfunctional CD39+ expression in TILs in cancer patients.